HISTORICAL LATERAL IRRIGATION FACILITIES AND WATER-RELATED TECHNOLOGIES IN SHUSHTAR AND DEZFUL-MILL, DUNGEON, GYRE, WATERWHEEL - Parviz Talaeyanpour; Hossein Moftakhari; Mirhadi Hosseini (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
According to various studies and researchers mills originate in Iran. Due to enjoying several rivers and five large streams in this part of the country, this technology has been used for making wheat flour since ancient times in the province of Khuzestan. Since the Sassanid Empire, historical cities such as Shushtar and Dezful have utilized the energy of water for a variety of purposes such as constructing numerous mills in these two counties due to their two large rivers, i.e. Karun and Dez. The greatest number of mills in Iran, either great in number or size, are located in this county, which resulted in creating a great industrial complex. After Shushtar, the second largest collection of mills of the country, either in terms of number or the technology (indirect energy transmission), is located in Dezful. Dungeon and Gyre are two techniques for water transmission that are used for irrigation and supplying water, which has been used for a long period of time in Iran. There are dungeons in Dezful with two types of application, i.e. dungeons used for irrigation of farms and dungeons used for irrigation of public bathrooms and houses. The technique, construction, measurements, and manner of utilization of these dungeons are different from the dungeons used in other parts of the country.